LEASING (Problema Praktek Al-Ijârah Kontemporer) - Atmadja, Dwi Surya (Khatulistiwa, 2012)
This article elaborates the practice of ijarah in the modern world. This article was triggered by the fact that there have been a lot of movements towards sharia economy lately. These movements are marked by the emergence of sharia economic organizations in Indonesia. In line with the goal of Islamic economic practices which is to bring prosperity for the entire humankind, the practice of ijarah must be able to carry out the mission. Meanwhile if we compare the practice of ijarah in the past to that of the present, there are challenges faced by those who currently practice sharia economy since sharia economy is more exploitative than conventional economy. Therefore, we need to consider the compatibility of the practice of ijarah in the past with that of the present.